Analysis of Ro-Ro Ship Performance Management at the Merak-Bakauheni Crossing Port - Evada Rustina; Rafdy Kaukabun Nufus; Sri Sayekti Lestari; Mochammad Sidiq Fathonni; Mochammad Sidiq; Sumarwanto (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The Merak Crossing Port with the Merak – Bakauheni route connects the islands of Java and Sumatra which is the busiest crossing port in Indonesia. The purpose of this study is to analyze the management of Ro-Ro ship performance at the Merak-Bakauheni Crossing Port, including analyzing the calculation of ship trip targets, analyzing the total, average and standard deviation of ship trip targets, and analyzing the trip achievement of each ship. This research was conducted using quantitative methods with qualitative descriptive techniques. Researchers use several data collection techniques, namely literature studies, observations, documentation and interviews. Researchers use data analysis techniques, namely quantitative analysis, namely to calculate the target of a ship's trip in one period of schedule, average and standard deviation. The calculation of the number of ship trips in one scheduled period is based on the number of ships that can operate in one scheduled period and the number of trip slots. Based on data processing and analysis, the results were obtained that the total one-period ship trip slots were 6,696 trips. The average trip grouping of piers I and II is 100 trips, the grouping of pier III is 102 trips, and the grouping of pier VI (executive) is 163 trips. While the standard deviation of the grouping of pier 1 is 0.68; the grouping of pier II is 0.72; the grouping of pier III is 0.91, and the grouping of pier VI (executive) is 4.61. From the realization of ship trips, it was found that the average ship at the Merak crossing port in March had not met the trip target that had been set. With a total of 39 ships or 67% of the total ships that lack trips and a total of 19 ships or 33% over-trip.